A multilevel hypernetworks approach to capture meso-level synchronisation processes in football. Issue 5 (3rd March 2020) - Ribeiro, João; Lopes, Rui; Silva, Pedro; Araújo, Duarte; Barreira, Daniel; Davids, Keith; Ramos, João; Maia, José; Garganta, Júlio
ABSTRACT: Understanding team behaviours in sports performance requires understanding the interdependencies established between their levels of complexity (micro-meso-macro). Previously, most studies examined interactions emerging at micro- and macro-levels, thus neglecting those emerging at a meso-level (reveals connections between player and team levels, depicted by the emergence of coordination in specific sub-groups of players–simplices during performance). We addressed this issue using the multilevel hypernetworks approach, adopting a cluster-phase method, to record player-simplice synchronies in two performance conditions where the number, size and location of goals were manipulated (first-condition: 6 × 6 + 4 mini-goals; second-condition: Gk + 6 × 6 + Gk). We investigated meso-level coordination tendencies, as a function of ball-possession (attacking/defending), field-direction (longitudinal/lateral) and teams (Team A/Team B). Generally, large synergistic relations and more stable patterns were observed in the longitudinal direction of the field than the lateral direction for both teams, and for both game phases in the first condition. The second condition displayed higher synchronies and more stable patterns in the lateral direction than the longitudinal plane for both teams, and for both game phases. Results suggest: (i) usefulness of hypernetworks in assessing synchronisation of teams at a meso-level; (ii) coaches may consider manipulating these task constraints to develop levels of local synchronies within teams.